Ketogenic diet inhibits neointimal hyperplasia by suppressing oxidative stress and inflammation - Xuefei Xu; Limin Xie; Lili Chai; Xiaoming Wang; Jinhu Dong; Jipei Wang; Pengwei Yang (Clinical and Experimental Hypertension, 2023)
Objective Neointimal hyperplasia is the primary mechanism underlying atherosclerosis and restenosis after percutaneous coronary intervention. Ketogenic diet (KD) exerts beneficial effects in various diseases, but whether it could serve as non-drug therapy for neointimal hyperplasia remains unknown. This study aimed to investigate the effect of KD on neointimal hyperplasia and the potential mechanisms. Methods and Results Carotid artery balloon-injury model was employed in adult Sprague-Dawley rats to induce neointimal hyperplasia. Then, animals were subjected to either standard rodent chow or KD. For in-vitro experiment, impacts of β-hydroxybutyrate (β-HB), the main mediator of KD effects, on platelet-derived growth factor BB (PDGF-BB) induced vascular smooth muscle cell (VSMC) migration and proliferation were determined. Balloon injury induced event intimal hyperplasia and upregulation of protein expression of proliferating cell nuclear antigen (PCNA) and α-smooth muscle actin (α-SMA), and these changes were significantly ameliorated by KD. In addition, β-HB could markedly inhibit PDGF-BB induced VMSC migration and proliferation, as well as inhibiting expressions of PCNA and α-SMC. Furthermore, KD inhibited balloon-injury induced oxidative stress in carotid artery, indicated by reduced ROS level, malondialdehyde (MDA) and myeloperoxidase (MPO) activities, and increased superoxide dismutase (SOD) activity. We also found balloon-injury induced inflammation in carotid artery was suppressed by KD, indicated by decreased expressions of proinflammatory cytokines IL-1β and TNF-α, and increased expression of anti-inflammatory cytokine IL-10. Conclusion KD attenuates neointimal hyperplasia through suppressing oxidative stress and inflammation to inhibit VSMC proliferation and migration. KD may represent a promising non-drug therapy for neointimal hyperplasia associated diseases.